Evidence for a Highly Dynamic West Antarctic Ice Sheet During the Pliocene. Issue 14 (20th July 2021) - Gohl, Karsten; Uenzelmann‐Neben, Gabriele; Gille‐Petzoldt, Johanna; Hillenbrand, Claus‐Dieter; Klages, Johann P.; Bohaty, Steven M.; Passchier, Sandra; Frederichs, Thomas; Wellner, Julia S.; Lamb, Rachel; Leitchenkov, German; ,
Abstract: Major ice loss in the Amundsen Sea sector of the West Antarctic Ice Sheet (WAIS) is hypothesized to have triggered ice sheet collapses during past warm periods such as those in the Pliocene. International Ocean Discovery Program (IODP) Expedition 379 recovered continuous late Miocene to Holocene sediments from a sediment drift on the continental rise, allowing assessment of sedimentation processes in response to climate cycles and trends since the late Miocene. Via seismic correlation to the shelf, we interpret massive prograding sequences that extended the outer shelf by 80 km during the Pliocene through frequent advances of grounded ice. Buried grounding zone wedges indicate prolonged periods of ice‐sheet retreat, or even collapse, during an extended mid‐Pliocene warm period from ∼4.2–3.2 Ma inferred from Expedition 379 records. These results indicate that the WAIS was highly dynamic during the Pliocene and major retreat events may have occurred along the Amundsen Sea margin. Plain Language Summary: Collapses of the West Antarctic Ice Sheet (WAIS) during past warm times are suggested to begin in the Amundsen Sea sector. During a drilling expedition of the International Ocean Discovery Program (IODP), deep‐sea sediments were retrieved from the Amundsen Sea. These sediment cores contain records of colder and warmer periods in the Pliocene (5.3–2.6 million years ago) which relate to the behavior of the WAIS. By analyzing seismic images that allow correlation of sediment layers from the drill sites to the continental shelf, we show that the shelf grew oceanward by 80 km due to the erosion of sediments below the WAIS and their deposition at the shelf break as the result of frequent Pliocene advances of grounded ice across the shelf. The shelf sediment layers contain grounding zone wedges predominantly formed during ice sheet retreat. The preservation of these grounding zone wedges testifies that they were not eroded by subsequent ice advances, with their burial requiring periods of prolonged WAIS retreat during warm intervals. This interpretation is consistent with our IODP drill core observations of a prominent decrease in terrigenous sedimentation between 4.2 and 3.2 million years ago, which indicates a highly dynamic WAIS during the Pliocene. Key Points: Seismic stratigraphic continental rise‐to‐shelf link from International Ocean Discovery Program (IODP) Expedition 379 drill sites on the Amundsen Sea rise Major prograding shelf growth in the Amundsen Sea Embayment by frequent grounded ice advances in the early Pliocene Extended period of ice sheet retreat in mid‐Pliocene (4.2–3.2 Ma) from buried grounding zone wedges on shelf and core records from rise